Influencing factors on the health of nurses-a regression analysis considering individual and organizational determinants in Germany - Jasmin Lützerath; Hannah Bleier; Gerrit Stassen; Andrea Schaller (BMC, 2023)
Abstract Background The care sector is characterized by high absenteeism of nursing care employees due to illness. Organizational determinants that can affect the mental health of nurses are known. Although nurses are confronted with different framework conditions in different care settings, there is a lack of comparative data in Germany. Methods The purpose of this study was to examined the relationship between work demands and employee health in different care settings. This cross-sectional survey was conducted between June and October 2021 in four acute care hospitals, seven inpatient care facilities, and five outpatient care services in Germany. 528 nursing care employees (acute care hospitals n = 234; inpatient care facilities n = 152; outpatient care services n = 142) participated in the survey (participation rate: 22.6%-27.9%). For each care setting, data was collected via questionnaire on individual determinants (gender, age, profession, working time), organizational work demands (quantitative workload, qualitative workload, organization of work, social work climate, after work situation, verbal violence, threats, physical violence) and employee health (subjective health status and work ability). Descriptive statistics and binary logistic regressions were performed. Results Increasing age (OR = 0.650, 95% CI = 0.424-0.996) as an individual determinant and organization of work (OR = 0.595, CI = 0.362-0.978) as an organizational determinant were negatively associated with subjective health. Furthermore, age (OR = 0.555, 95% CI = 0.353-0.875), a demanding organization of work (OR = 0.520, CI = 0.315-0.858), increasing quantitative workloads (OR = 0.565, CI = 0.343-0.930) and a poorer perceived social work climate (OR = 0.610, CI = 0.376-0.991) were associated with lower work ability. Conclusions Based on the study results, health programs should target both individual and organizational factors. The findings seem to support the importance to include nursing care employees in the planning process, as it can have an impact on their health. Trial registration The project was registered in the German Clinical Trial Register (DRKS00024961, 09/04/2021).